Ответы и объяснения

Лучший Ответ!
2013-04-15T11:40:16+00:00

-7x+10x-15=6                5x-21+7x=2x+11                x^2-3x-2x+6=x^2+x      x^2+6x+4x+24-x^2=30

3x=15+6                          5x+7x-2x=11+21              x^2-x^2-3x-2x-x=-6        x^2-x^2+6x+4x=30-24

3x=21                               10x=32                               -6x=-6                                10x=14

x=7                                      x=3.2                                   x=1                                       x=1.4